Some Physical Characteristics and Nutritional Composition of the Seeds of Wild Pepper (Erythrococca anomala, Benth) - Akande, E. A.; Adegoke, G. O.; Mathookoc, F. C. (Biological Sciences - PJSIR, 2008)
. Study of physical properties and nutritional components of whole and powdered wild pepper seeds (Erythrococca anomala,Benth) revealed that the seeds have good parameters for machineability. The contents of moisture, ash, protein, lipid and carbohydrate and major and trace minerals were found in functional quantities, while the heavy metals were negligible or absent. Thus the seeds are potential source of nutrients and can be used as additive in food product development.